Optical extinction coefficients of gold nanoparticle aggregates by small angle X-ray scattering (SAXS) - Chong, J. C. (Penerbit Universiti Sains Malaysia, 2017)
The size distribution of gold hydrosol aggregates induced by ascorbic acid has been characterised by small angle x-ray scattering (SAXS). The results are used to compute the extinction coefficients around the localised surface plasmon resonance (LSPR) wavelengths and verified by comparing experimental extinction spectra obtained via spectrophotometry. Citrate refluxed gold nanoparticles with initial ionic ratio of 0.94 measured by fitting an averaged intensity profile from two scattering lengths exhibit lognormal distribution with mean diameter of 27.4 nm (σd = 14.4 nm), while ascorbic acid induced agglomeration on gold nanoparticles at pH of 3.2 has mean diameter of 51.2 nm (σd = 19.2 nm). Both experiment and simulated optical extinction shows agreement in LSPR peak wavelength corresponding to their respective mean particle sizes.